2017
DOI: 10.1111/bjop.12259
|View full text |Cite
|
Sign up to set email alerts
|

How intention and monitoring your thoughts influence characteristics of autobiographical memories

Abstract: Involuntary autobiographical memories come to mind effortlessly and unintended, but the mechanisms of their retrieval are not fully understood. We hypothesize that involuntary retrieval depends on memories that are highly accessible (e.g., intense, unusual, recent, rehearsed), while the elaborate search that characterizes voluntary retrieval also produces memories that are mundane, repeated or distant - memories with low accessibility. Previous research provides some evidence for this 'threshold hypothesis'. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
87
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(98 citation statements)
references
References 45 publications
10
87
1
Order By: Relevance
“…The finding that voluntary retrieval leads to a higher frequency of memories than involuntary retrieval at the shortest retention interval replicates earlier findings from our lab using a very similar paradigm (Berntsen et al, 2013;Staugaard & Berntsen, 2014). However, several studies investigating everyday autobiographical memory have found involuntary memories to be slightly more recent than voluntary memories (Barzykowski & Staugaard, 2018;Berntsen, 1998;Finnbogadóttir & Berntsen, 2011;Johannessen & Berntsen, 2010). One explanation for this apparent discrepancy could be that involuntary memories largely rely on environmental cues, whereas voluntary memories are less constrained by the immediate environment (Berntsen, 2009;Rasmussen, Johannessen, & Berntsen, 2014).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The finding that voluntary retrieval leads to a higher frequency of memories than involuntary retrieval at the shortest retention interval replicates earlier findings from our lab using a very similar paradigm (Berntsen et al, 2013;Staugaard & Berntsen, 2014). However, several studies investigating everyday autobiographical memory have found involuntary memories to be slightly more recent than voluntary memories (Barzykowski & Staugaard, 2018;Berntsen, 1998;Finnbogadóttir & Berntsen, 2011;Johannessen & Berntsen, 2010). One explanation for this apparent discrepancy could be that involuntary memories largely rely on environmental cues, whereas voluntary memories are less constrained by the immediate environment (Berntsen, 2009;Rasmussen, Johannessen, & Berntsen, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…In addition to this novel finding, we replicated effects from earlier work: namely, that voluntary retrieval was more effective overall than involuntary retrieval (Berntsen et al, 2013), that unique cues were more effective than repeated cues (Berntsen et al, 2013;Hunt & Smith, 1996;Mäntylä & Nilsson, 1988), and that involuntary retrieval was considerably faster than voluntary retrieval (Barzykowski & Staugaard, 2018;Berntsen et al, 2013;Schlagman & Kvavilashvili, 2008;Staugaard & Berntsen, 2014). We also found that retrieval time increased with increased retention interval in response to unique cues, but not in response to repeated cues, which suggests that the unique associations might become less accessible than the repeated associations as time passes.…”
Section: Discussionsupporting
confidence: 81%
“…The explicit nature of this method also allows one to explore the latency between stimuli and the thoughts that are cued by it (see . This method is limited, however, by increasing the level of self-monitoring processes than would be normally expected (Smallwood & Schooler, 2006), which may alter the characteristics and frequency of certain recorded thoughts (Vannucci, Batool, Pelagatti, & Mazzoni, 2014; see also Barzykowski & Niedźwieńska, 2016;Barzykowski & Staugaard, 2018). Self-caught recording may also be affected by social desirability, because participants are informed about the nature of thoughts that the researcher is interested in.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Slides were presented for 2.5 s with short verbal phrases (e.g., driving a car, swimming in the sea ) displayed in the centre of each slide. There were approximately equal numbers of neutral ( N = 134), positive ( N = 133), and negative ( N = 133) phrases, that constituted the final pool of 400 phrases, which were randomly selected from the pool of 800 phrases used in previous studies (e.g., Barzykowski & Niedźwieńska, 2016 , 2018a ; Barzykowski & Staugaard, 2016 , 2018 ). 4 While the random selection of word phrases from the pool was exactly the same for all participants, the order was randomized for each participant.…”
Section: Methodsmentioning
confidence: 99%